VIVÊNCIAS A PARTIR DE UM PROJETO DE EXTENSÃO EM LÍNGUA FRANCESA NA MODALIDADE ORAL - Leonel, Ana Rosa (Intercâmbio, 2010)
This paper intends to comment on experience lived in an extension project that had the objective of providing opportunity to use French orally. We shall report the main features of the otivation of the project and the development of some activitiesthat took place during the project as well as the results of the course.